Gambaran gangguan pemusatan perhatian pada remaja gamers di Manado periode November 2014 â€“ Desember 2014 - Kaseger, Kevin A.; Khosama, Herlyani; Mahama, Corry N. (e-CliniC, 2016)
Abstract: Attention deficit disorders (ADD) is a medical disorder that has its own characteristics and tends to be hereditary. Generally, there are three types of behavior associated with this disorder, namely: lack of surrounding attention (inattentiveness), easily distracted (distractibility), and impulsive attitude (impulsiveness). This study was aimed to obtain the prevalence of ADD among adolescent gamers. This was a descriptive-quantitative study with a cross-sectional design. This study was carried out on regular gamers aged 12-15 years who were students of junior high schools. The total respondents in this study were 30 regular gamer teenagers. The digit span, backward digit span, and the stroop test were performed on all respondents. The results showed that among teenagers who played video games more than 1 time per week there were 36.67% with attention deficit disorders.Keywords: ADD, videogames, adolescents, digit span, backward digit span, stroop testÂ Abstrak: Gangguan pemusatan perhatian (GPP) adalah suatu kelainan medis yang memiliki ciri tersendiri dan cenderung merupakan keturunan. Secara umum terdapat tiga jenis perilaku yang dikaitkan dengan kelainan ini, yaitu: sikap kurang memperhatikan sekeliling (inattentiveness), mudah terganggu (distractibility), dan sikap menurutkan kata hati (impulsiveness). Penelitian ini bertujuan untuk mendapatkan prevalensi GPP di kalangan remaja gamers. Jenis penelitian ialah deskriptif-kuantitatif dengan desain potong lintang. Penelitian ini dilakukan pada remaja regular gamers berusia 12-15 tahun yang masih duduk di bangku SMP dengan total 30 remaja regular gamers sebagai responden. Pada responden dilakukan pemeriksaan digit span, backward digit span, dan stroop test. Hasil penellitian memperlihatkan bahwa dari ketiga macam pemeriksaan tersebut yang dilakukan pada remaja yang bermain videogame lebih dari 1 kali per minggu didapatkan GPP rata-rata 36,67%. Kata kunci: GPP, videogame, remaja, digit span, backward digit span, stroop test.